Prevalence of Atrial Fibrillation in Patients with Ischemic Stroke and its Effect on Functional Outcome. - Karki, Binod; Pande, Prakash Raj; Sharme, Arun; Deo, Rajeeb Kumar (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Stroke is third most common cause of death worldwide characterized by rapidly progressiveclinical symptoms and signs of focal or global loss of cerebral functions. Among various risk factors, atrialÞ brillation is one which affects the functional outcome. The objective of this study was to Þ nd out the prevalenceof atrial Þ brillation in patients with ischemic stroke in Nepalese context and its effect on the functional outcomeusing modiÞ ed Barthel index. Methods: Cross sectional analytical study was conducted in a tertiary level hospital over a period of oneyear from July 2011 to June 2011. All the patients who were admitted with the diagnosis of ischemic strokeduring the study period were included in the study. Presence of atrial Þ brillation was conÞ rmed by 12 leadelectrocardiograms. The parameters of patients with and without atrial Þ brillation were compared. Results: Total of 75 cases of ischemic stroke was identiÞ ed, out of which nine had atrial Þ brillation in the ECGwhich makes a prevalence of 12%. Among 75 patients, 41% were female and 59% were male with the meanage of presentation was 63. Majority of patients (62.8%) were above 60 years of age. The functional severityas assessed from Barthel index (mean) was 36.11 and 55.83 respectively in those having ischemic stroke withatrial Þ brillation and without atrial Þ brillation with 88.9% of patients with AF below the score of 40 ( p<0.0001). Conclusions: In our population, the prevalence of atrial Þ brillation in patients with ischaemic stroke is 12%and Barthel index of patiens with stroke and atrial Þ brillation is signiÞ cantly lower than the patients withoutatrial Þ brillation. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12916